Effects of DNA methylation inhibitors on light-induced circadian clock plasticity - Suil Kim; Douglas G. McMahon (Neurobiology of Sleep and Circadian Rhythms)
The suprachiasmatic nucleus (SCN) of the hypothalamus is a principal light-responsive circadian clock that adjusts circadian rhythms in mammalian physiology and behavior to changes in external light signals. Although mechanisms underlying how light acutely resets the timing of circadian rhythms have been characterized, it remains elusive how light signals induce lasting changes in circadian period, known as period after-effects. Here we have found that the period after-effects on circadian behavior of changing photoperiods are blocked by application of the DNA methyltransferase inhibitor RG108 near the SCN. At the level of single light pulses acting as clock-resetting stimulations, RG108 significantly attenuates period after-effects following acute phase shifts in behavioral rhythms in vivo, and blocks period after-effects on clock gene rhythms following phase resetting by the vasoactive intestinal peptide in the isolated ex vivo SCN. In addition, the DNA methyltransferase inhibitor SGI-1027 blocked period after-effects of optogenetic neuronal stimulation on ex vivo SCN rhythms. Acute clock resetting shifts themselves, however, do not appear to require DNA methylation at the SCN and behavioral levels, in contrast to subsequent period plasticity. Our results demonstrate that DNA methylation inhibitors block light-induced period after-effects in response to photoperiods and single light pulses. Together with previous studies showing that DNA methylation in the SCN is essential for period after-effects of non-24hr light cycles (T-cycles), this suggests that DNA methylation in the SCN may be a widespread mechanism of light-induced circadian period plasticity.